Effects of benzodiazepines administration on identification of facial expressions of emotion: a meta-analysis. - Garcez, Helena; Fernandes, Carina; Barbosa, Fernando; Pereira, Mariana R.; Silveira, Celeste; Marques-Teixeira, João; Gonçalves, Ana R. (Psychopharmacology, 2020)
Rationale: Benzodiazepines, a class of commonly prescribed drugs, were shown to cause cognitive impairments in several domains. However, the effect of benzodiazepines on social cognition is still unclear. Objectives: In order to clarify how benzodiazepines administration affects the identification of facial expressions of emotion (FEE), we conducted a meta-analysis of 8 empirical studies (N = 153 benzodiazepines, N = 153 placebo). Results: Results showed that participants receiving benzodiazepines were less accurate at identifying facial expressions of anger compared with those receiving placebo (M = − 0.52). Regarding the remaining facial expressions, the meta-analysis did not reveal significant differences between the groups. Conclusions: We discuss several factors that may explain the differences in the identification of emotions in facial expressions associated with benzodiazepines administration. Additionally, the relevance of assessing the effects of benzodiazepines when used on a long-term basis is addressed.